Medical management of obesity and overweigth in childhood - Carmen Emilia Guerra Cabrera; Ailyn del Carmen Cabrera Romero; Inti Santana Carballosa; Alina González Hermida; Pilar Almaguer Sabina; Teresa Urra Coba (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2009)
-